BENTUK PENYAJIAN MUSIK GAMELAN PADA TARI SEINGGOK SEPEMUNYIAN DI SANGGAR SEINGGOK SEPEMUNYIAN KOTA PRABUMULIH - Anggraini, Ranita; A Heyanto, A Heyanto; Yelli, Nofroza (Besaung : Jurnal Seni Desain dan Budaya, 2021)
The problem in this research is how the form of Gamelan Music Presentation in Seinggok Sepemunyian Dance at Sanggar Seinggok Sepemunyian, Prabumulih City. The purpose of this study was to determine and describe the form of presenting gamelan music in the Seinggok Sepemunyian dance at Sanggar Seinggok Sepemunyian, Prabumulih City. The method used in this research is descriptive qualitative. This research was conducted at Sanggar Seinggok Sepemunyian, Prabumulih City. In this study, researchers used data collection techniques by means of observation, interviews and documentation. The technique used is 1) the observation technique, namely observing directly the form of gamelan music in the presentation of the seinggok sepemunyian dance, 2) the interview technique is carried out by giving questions to the source who knows a lot about gamelan music, as well as the management of the Seinggok Sepemunyian Studio. 3) documentation technique, namely collecting data in the form of documents related to gamelan music in the presentation of the Seinggok Sepemunyian dance including audio and visual data. The results of this study indicate that Sanggar Seinggok Sepemunyian in gamelan music in the presentation of the Seinggok Sepemunyian dance tells about musical performances that will start until the end of the music show and the Seinggok Sepemunyian Dance is complete, where there is a musical concept in playing musical instruments such as drums face two.